Greenhouse climate model : an aid to estimate the influence of supplemental lighting on greenhouse climate - Binotto, Marco 1987- (2012)
GeoGreenhouse project involves the construction of a greenhouse for growing tomatoes in Iceland. The first stage consists of a gross area of five hectares. Due to the peculiarities of such project and because of the unique weather, a greenhouse climate model is advisable to analyze various design solutions. Iceland's weather has a seasonal change in the length of day and night, creating unique weather phenomena. In midwinter, there is a period where darkness prevails. In midsummer, daylight takes over and night darkness is almost absent during June and July. Artificial lighting and movable blackout screen are therefore needed to have a year round production. Replacement lighting requires a high density of lighting devices which implicates a big heat gain due their losses. Understanding the influence of the artificial lighting on the greenhouse climate is necessary in order to set up an adequate control strategy. The developed model includes, in addition of the greenhouse structure, all the equipments for climate controlling, such as: blackout screens, artificial lighting, heating system, fogging system, roof vents, and mechanical ventilation. Simulation results show that the requirements to maintain the desired indoor climate change depending on the mutual relation between the blackout screen position and the outdoor solar radiation. For instance, if the crop night-phase occurs when the external radiation is low, turning off the lamps is sufficient to lower the air temperature in the greenhouse; while, if the crop night-phase occurs at noon to lower the indoor temperature it is necessary to open the roof vents. A control strategy which ensures the desired indoor climate has been investigated. At the beginning, the control methodology considered a 24 hours cycle for the crop photoperiod. A deeper analysis showed a big disparity between the sunlight intercepted by the plant canopy of one zone of the greenhouse and the others. Since the irradiation on canopy leaves is the factor which has the main influence on crop ...